A Reciprocal Interaction between β-Catenin and Osterix in Cementogenesis - Hwajung Choi (Nature Portfolio, 2017)
Abstract Although accumulating evidence indicates that both β-catenin and osterix (Osx) are essential for bone and tooth development, few studies have investigated the interaction of these two key proteins in the context of cementogenesis. In this study, we used transgenic mice with constitutively active β-catenin and inactive Osx in the dental mesenchyme to address this question. We found that cementoblasts with constitutively active β-catenin require Osx to produce excessive cellular cementum, and that ablation of Osx prevents this abnormal accumulation. Importantly, cementoblasts transduced with retrovirus expressing constitutively active β-catenin exhibited upregulation of Osx expression through direct binding to the promoter region of Osx. Osx regulates Lef1 expression and consequently could regulate T-cell factor/lymphoid enhancer factor (Tcf/Lef) binding activity in Wnt/β-catenin signaling. However, the loss of Tcf/Lef binding activity by Osx ablation was not rescued by transduction of retrovirus expressing constitutively active β-catenin or ectopic Lef1 overexpression. These results suggest that the Tcf/Lef binding activity of Wnt/β-catenin signaling is Osx-dependent during cementogenesis. Moreover, Osx differentially regulates the expression of various Tcf family members, suggesting that Osx regulates cementogenesis by utilizing various Tcf/Lef-dependent mechanisms. This is the first report to show that downstream Osx signaling through Tcf/Lefs is critical for cementogenesis.